Grain Yield and Quality of Foxtail Millet (Setaria italica L.) in Response to Tribenuron-Methyl. - Na Ning (PLoS ONE, 2015)
Foxtail millet (Setaria italica L.) is cultivated around the world for human and animal consumption. There is no suitable herbicide available for weed control in foxtail millet fields during the post-emergence stage. In this study, we investigated the effect and safety of the post-emergence herbicide tribenuron-methyl (TBM) on foxtail millet in terms of grain yield and quality using a split-plot field design. Field experiments were conducted using two varieties in 2013 and 2014, i.e., high-yielding hybrid Zhangzagu 10 and high-quality conventional Jingu 21. TBM treatments at 11.25 to 90 g ai ha(-1) reduced root and shoot biomass and grain yield to varying degrees. In each of the two years, grain yield declined by 50.2% in Zhangzagu 10 with a herbicide dosage of 45 g ai ha(-1) and by 45.2% in Jingu 21 with a herbicide dosage of 22.5 g ai ha(-1) (recommended dosage). Yield reduction was due to lower grains per panicle, 1000-grain weight, panicle length, and panicle diameter. Grain yield was positively correlated with grains per panicle and 1000-grain weight, but not with panicles ha(-1). With respect to grain protein content at 22.5 g ai ha(-1,) Zhangzagu 10 was similar to the control, whereas Jingu 21 was markedly lower. An increase in TBM dosage led to a decrease in grain Mn, Cu, Fe, and Zn concentrations. In conclusion, the recommended dosage of TBM was relatively safe for Zhangzagu 10, but not for Jingu 21. Additionally, the hybrid variety Zhangzagu 10 had a greater tolerance to TBM than the conventional variety Jingu 21.